Pendekatan Economic Analysis of Law (EAL) dalam Hukum untuk Pembangunan Indonesia - Indah Pangestu Amaritasari (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Development in Indonesia is currently marked by a variety of economic growth. Indonesia's national development is a development paradigm that is built on the experience of Pancasila, namely the development of the whole Indonesian human being and the development of the Indonesian people as a whole and Article 33 of the 1945 Constitution. Thus, the RPJMN includes the Sustainable Development Goals (SDGs). The focus of development is welfare, which cannot be separated from issues economy. In this framework, policy tools are needed, especially the economic sector that can support welfare and achieve justice. This Economic Analysis of Law (EAL) approach can be used as a means to see the role of law in supporting the achievement of prosperity and justice through an economic perspective for the development. This research is normative-doctrinal by exploring legal products and curating literature (written, visual, and audiovisual) to map out the role of law in development using the EAL approach. The findings from this study indicate that EAL approach can be used as a tool to critise and analyse legislations and situation which are contribute significantly to development, namely: the economic policy and legislation, the restorative justice sector, and corruption.